Severe Vitamin D Deficiency in Saudi Patients with Type 2 Diabetes Mellitus - K.S. Aljabri; S. A. Bokhari (Journal of Obesity Management, 2019)
Introduction It has been demonstrated that vitamin D deficiency is associated with type 2 diabetes mellitus (T2DM). We conducted a cross sectional study to investigate the prevalence severe vitamin D deficiency in patients with T2DM. Method A cross-sectional single centre study was conducted in 4053 patients with T2DM. Patients with T2DM attended the Diabetes Centre at King Fahad Armed Forces Hospital, Jeddah, Saudi Arabia between January 2018 and December 2018 were recruited. Results There were 4053 patients with T2DM, 1145 male and 2908 female (28 % vs.72% respectively). The mean age was 53.9 ±16.5 years. The mean and median 25-OHD concentrations were 57.8±30.5 and 51.9 respectively. Severe vitamin D deficiency (25-OHD<25 nmol/l) was found in 1916 (9.5%). Moreover, severe vitamin D deficiency was not statistically significant more prevalent among females than males with male to female ratio 1:2.3 (70% vs. 30% respectively, p=0.6). In addition, severe vitamin D deficient patients were statistically significant younger than non-vitamin D deficient (48.0±16.7 vs. 54.6±16.3 respectively, p<0.0001). Severe vitamin D deficient patients have statistically significant higher HbA1c than non-vitamin D deficient (8.3 ±2.3 vs. 7.6±1.9 respectively, p<0.0001). The mean 25-OHD was upward as age advanced with highest frequency of vitamin D deficiency was found in the age group ≥60 years (27%) with males statistically significant most frequent than females in the age group ≥60 years (39 s, 22 respectively, p=0.003). Regression analysis of odd ratio of risk factors for patients with severe vitamin D deficiency showed that age and HbA1c were statistically significant associated with vitamin D deficiency. Conclusions The prevalence of severe vitamin D deficiency in patients with T2DM is low and that more females with T2DM are affected with vitamin D deficiency than males.
Keywords: Vitamin D Deficiency